Pain Catastrophizing and Pain Health-Related Quality-of-Life in Endometriosis. Issue 4 (April 2018) - McPeak, Allison E.; Allaire, Catherine; Williams, Christina; Albert, Arianne; Lisonkova, Sarka; Yong, Paul J.
Abstract : Objectives: To determine if pain catastrophizing is independently associated with pain health-related quality-of-life (HRQoL) in women with endometriosis, independent of potential confounders. Materials and Methods: Analysis of cross-sectional baseline data from a prospective database at a tertiary referral center for endometriosis/pelvic pain. Referrals to the center were recruited between December 2013 to April 2015, with data collected from online patient questionnaires, physical examination, and review of medical records. The primary outcome was HRQoL as measured by the 11-item pain subscale of the Endometriosis Health Profile-30 questionnaire. The Pain Catastrophizing Scale was the independent variable of interest. Other independent variables (potential confounders) included other psychological measures, pain severity, comorbid pain conditions, and social-behavioral and demographic variables. Multivariable linear regression was used to control for these potential confounders and assess independent associations with the primary outcome. Results: In total, 236 women were included (87% consent rate). The mean age was 35.0±7.3 years, and 98 (42%) had stage I to II endometriosis, 110 (47%) had stage III to IV endometriosis, and 28 (11%) were of unknown stage after review of operative records. Regression analysis demonstrated that higher pain catastrophizing ( P <0.001), more severe chronic pelvic pain ( P <0.001), more severe dysmenorrhea ( P <0.001), and abdominal wall pain (positive Carnett test) ( P =0.033) were independently associated with worse pain HRQoL. Discussion: Higher pain catastrophizing was associated with a reduced pain HRQoL in women with endometriosis at a tertiary referral center, independent of pain severity and other potential confounders.